2022
DOI: 10.1093/jxb/erac487
|View full text |Cite
|
Sign up to set email alerts
|

Past, present, and future of genetic strategies to control tolerance to the main fungal and oomycete pathogens of grapevine

Abstract: The production of high-quality wines is strictly related to the correct management of the vineyard, which guarantees good yields and grapes with the right characteristics required for subsequent vinification. Winegrowers face a variety of challenges during the grapevine cultivation cycle: the most notorious are fungal and oomycete diseases such as downy mildew, powdery mildew, and gray mold. If not properly addressed, these diseases can irremediably compromise the harvest, with disastrous consequences for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 177 publications
0
7
0
Order By: Relevance
“… 83 In our view, the potential use of new biotechnological approaches for either loss-of-function and gain-of-function applications, such as cisgenesis (for conspecific gene transfer or introgression) and genome editing (for endogenous gene knockout or silencing and gene editing or replacement) will assume strong relevance in plant breeding programs dealing with tolerance to abiotic stresses, as these methods would allow direct intervention at the genomic level in any variety/cultivar without changing its genetic background. 84 We are confident that these applications of genomics combined with platforms of phenomics represent the right answer for the future of agriculture as it can provide a key contribution to the development of new plant genotypes and molecular assays for the main crop species to implement and predict the agronomic value-added of plant varieties expressing resilient traits and phenotypes, including those for salt tolerance.…”
Section: Breeding For Salt Tolerance In Crop Plantsmentioning
confidence: 99%
“… 83 In our view, the potential use of new biotechnological approaches for either loss-of-function and gain-of-function applications, such as cisgenesis (for conspecific gene transfer or introgression) and genome editing (for endogenous gene knockout or silencing and gene editing or replacement) will assume strong relevance in plant breeding programs dealing with tolerance to abiotic stresses, as these methods would allow direct intervention at the genomic level in any variety/cultivar without changing its genetic background. 84 We are confident that these applications of genomics combined with platforms of phenomics represent the right answer for the future of agriculture as it can provide a key contribution to the development of new plant genotypes and molecular assays for the main crop species to implement and predict the agronomic value-added of plant varieties expressing resilient traits and phenotypes, including those for salt tolerance.…”
Section: Breeding For Salt Tolerance In Crop Plantsmentioning
confidence: 99%
“…In this regard, the arrangement of genes on corresponding chromosomes, which is established through recombination events between different genetic markers, is known as genetic map. The progressive development of a multitude of molecular markers allowed the refinement of genetic maps ( Pirrello et al., 2023 ). SSRs, Random Amplified polymorphic DNA (RAPD), Amplified Fragment Length Polymorphism (AFLP), RFLP (Restriction fragment length polymorphism), Sequence Characterized Amplified Regions (SCARs) and SNP were over time exploited to accomplish dense genetic maps, aimed at the detection of QTLs (Quantitative Trait Locus) for specific traits of interest ( Adam-Blondon et al., 2004 ; Fischer et al., 2004 ; Welter et al., 2007 ; Emanuelli et al., 2013 ).…”
Section: Grapevine Cross Breeding Populationsmentioning
confidence: 99%
“…From then on, a multitude of studies and research have been conducted, till the publication of more than 160 different grapevine genetic maps, each of them based on one type or more of molecular markers. In this regard, SSRs are still the best markers to compile genetic maps and understand genotype-phenotype relationships due to their stability and codominance, and moreover for the high transferability among grapevine genotypes ( Vezzulli et al., 2019 ; Pirrello et al., 2023 ). The first two dense SSRs based genetic maps are those developed by Riaz et al.…”
Section: Grapevine Cross Breeding Populationsmentioning
confidence: 99%
“…For example, Burdon et al (2014) reported that the resistant genes against rust that could potentially be stacked in wheat cultivars may have already been used singly in one or more of the breeding programs around the world. Similarly, winegrowers can now plant pyramided cultivars stacking the resistance factors Rpv1 and Rpv3 to downy-mildew (Pirrello et al, 2023). If Rpv1 has never been deployed previously, Rpv3 was present in many of the interspecific hybrids planted at the beginning of the 20 th century.…”
Section: Introductionmentioning
confidence: 99%